+0

Given f(x)=3x 2 +5 and g(x)=x−2 .

+2
1492
1

Given f(x)=3x2+5 and g(x)=x−2 .

What is (fg)(x) ?

A. 3x3−10

B. −3x2+x−7

C. 3x3−6x2+5x−10

D. 3x2−x+7

Given f(x)=2x2−5x−3 and g(x)=2x2+x .

What is (fg)(x) ? Feb 12, 2018

#1
+2

First one:

(3X^2 +5)(x-2) = 3x^3 - 6x^2 +5x - 10

Second one is written incorrectly, I think you meant f/g(x)

f(x) = 2x^2-5x-3  =  (2x+1)(x-3)

then   f/g =   (2x+1)(x-3)  /  (x)(2x +1)          x cannot equal 0 or -1/2  because the denominator would be ZERO

Simplify to     (x-3)/x                       (the (2x+1)'s  'cancel out')

Feb 12, 2018
edited by Guest  Feb 12, 2018

#1
+2

First one:

(3X^2 +5)(x-2) = 3x^3 - 6x^2 +5x - 10

Second one is written incorrectly, I think you meant f/g(x)

f(x) = 2x^2-5x-3  =  (2x+1)(x-3)

then   f/g =   (2x+1)(x-3)  /  (x)(2x +1)          x cannot equal 0 or -1/2  because the denominator would be ZERO

Simplify to     (x-3)/x                       (the (2x+1)'s  'cancel out')

ElectricPavlov Feb 12, 2018
edited by Guest  Feb 12, 2018